Heparin‐induced thrombocytopenia: Construction of a pretest diagnostic score derived from the analysis of a prospective multinational database, with internal validation. (14th June 2021) - Tardy‐Poncet, Brigitte; de Maistre, Emmanuel; Pouplard, Claire; Presles, Emilie; Alhenc‐Gelas, Martine; Lasne, Dominique; Horellou, Marie‐Hélène; Mouton, Christine; Serre‐Sapin, Anne; Bauters, Anne; Nguyen, Philippe; Mullier, François; et al.
Abstract: Background: Diagnosis of heparin‐induced thrombocytopenia (HIT) requires pretest probability assessment and dedicated laboratory assays. Objective: To develop a pretest score for HIT. Design: Observational; analysis of prospectively collected data of hospitalized patients suspected with HIT (ClinicalTrials.gov NCT00748839). Setting: Thirty‐one tertiary hospitals in France, Switzerland, and Belgium. Patients: Patients tested for HIT antibodies (2280 evaluable), randomly allocated to derivation and validation cohorts. Measurements: Independent adjudicators diagnosed HIT based on the prospectively collected data and serotonin release assay results. Results: Heparin‐induced thrombocytopenia was diagnosed in 234 (14.7%) and 99 (14.5%) patients in the two cohorts. Eight features were associated with HIT (in brackets, points assigned for score calculation of the score): unfractionated heparin (1); therapeutic‐dose heparin (1); cardiopulmonary bypass (cardiac surgery) (2); major trauma (3); 5‐ to 21‐day interval from anticoagulation initiation to suspicion of HIT (4); ≥40% decrease in platelet count over ≤6 days (3); thrombotic event, arterial (3) or venous (3). The C‐statistic was 0.79 (95% CI, 0.76–0.82). In the validation cohort, the area under the receiver operating characteristic curve was 0.77 (95% CI, 0.74–0.80). Three groups of scores were defined; HIT prevalence reached almost 30% in the high‐probability group. Limitation: The performance of the score may depend on settings and practices. Conclusion: The objective, easy‐to‐collect, clinical features of HIT we evidenced were incorporated into a pretest score, which may guide clinical decisions regarding diagnostic testing and anticoagulation.